Impact of Inherited Thrombophilia on Pregnancy Complications and the Role of Low-Molecular-Weight Heparin Therapy: A Case–Control Study - Dragana Maglic; Vesna Mandic-Markovic; Zeljko Mikovic; Rastko Maglic; Radomir Anicic; Milica Mandic (Medicina)
Background and Objectives: Inherited thrombophilia (IT) increases the risk of adverse pregnancy outcomes, but the benefit of low-molecular-weight heparin (LMWH) prophylaxis remains debated. This study aimed evaluate the effect of LMWH by analyzing outcomes in women with IT who received LMWH versus those who did not and also compare pregnancy complication rates before and after inherited thrombophilia diagnosis. Materials and Methods: We conducted a retrospective case–control study including 276 pregnant women with inherited thrombophilia and prior pregnancy complications and 276 healthy pregnant controls on delivery. The main outcome was the incidence of complications: preterm rupture of membranes, oligohydramnios, fetal growth restriction, preterm delivery, stillbirth, HELLP syndrome, gestational hypertension, deep vein thrombosis, and recurrent pregnancy loss. The effect of LMWH was assessed by comparing complication rates among inherited thrombophilia patients who received therapy versus those who did not. Results: Women with IT were older, had higher BMI, delivered earlier, and had neonates with lower birth weight compared to controls. In current pregnancies, LMWH was associated with reduced rates of preterm delivery, fetal growth restriction, gestational hypertension, and recurrent pregnancy loss, especially in factor V Leiden carriers. LMWH had little effect on low-risk genotypes and was not independently associated with outcome reduction. Conclusions: LMWH prophylaxis should be reserved for high-risk women with IT. Routine use in all IT pregnancies is not justified and may cause unnecessary risks and costs. Early screening, risk stratification, and individualized care are essential to optimize outcomes.